Genetics of the ovarian reserve - Pelosi, Emanuele; Forabosco, Antonino; Schlessinger, David (Frontiers in Genetics, 2015)
Primordial follicles or non-growing follicles (NGFs) are the functional unit of reproduction, each comprising a single germ cell surrounded by supporting somatic cells. NGFs constitute the ovarian reserve, prerequisite for germ cell ovulation and the continuation of the species. The dynamics of the reserve is determined by the number of NGFs formed and their complex subsequent fates. During the reproductive lifespan, the ovarian reserve progressively diminishes due to follicle atresia as well as recruitment, maturation, and ovulation. The depletion of the ovarian reserve is the major determining driver of menopause, which ensues when the number of primordial follicles falls below a threshold of ~1,000. Therefore, genes and processes involved in follicle dynamics are particularly important to understand the process of menopause, both in the typical reproductive lifespan and in conditions like primary ovarian insufficiency (POI), defined as menopause before age 40. Genes and their variants that affect the timing of menopause thereby provide candidates for diagnosis of and intervention in problems of reproductive lifespan. We review the current knowledge of processes and genes involved in the development of the ovarian reserve and in the dynamics of ovarian follicles.